Research on the Impact of Interest Rate and Virtual Finance Reform on GDP Growth Based on Error Correction Model. (17th January 2022) - Zhang, Bo; Tao, Meichen
Abstract : In the context of the virtual economy, monitoring and controlling the operation of the virtual economy to prevent excessive asset bubbles due to inherent volatility and minimize the harm to the macroeconomy is one of the important tasks of economic development. This study applies the error correction model to the analysis of GDP growth factors, improves the algorithm to adapt it to the needs of GDP growth analysis, and constructs an analysis model of the impact of interest rate and virtual financial reforms on GDP growth. Moreover, this study combines data analysis to verify the performance of the model in this study. Through experimental analysis, we can see that the error correction model proposed in this study can play an important role in the analysis of GDP growth factors. At the same time, this study verifies that virtual financial reform and interest rate reform can have a certain impact on GDP growth and have a certain degree of relevance.